The Role of Gasotransmitters In the Amelioration of Arsenic Toxicity in Plants: Biology and Biotechnology - Singh, Vijay Pratap; Tripathi, Durgesh Kumar; Fotopoulos, Vasileios; Batista, Bruno Lemos; Fuentes, Gonzalo Tortella; Lobato, Allan Klynger Da Silva (My University, 2023)
The Role of Gasotransmitters In the Amelioration of Arsenic Toxicity in Plants: Biology and Biotechnology, in the Plant Gasotransmitter series, provides research on how gasotransmitters can reduce the stress faced by plants through arsenic contamination. With a strong focus on metabolic processes, the book presents the various pathways and mechanisms associated with gasotransmitters as part of arsenic amelioration. Initial chapters discuss the effects of arsenic on the plant genome and metabolome, as well as the mechanisms behind the uptake and translocation of arsenic in plants. The book then takes a deep dive into the role of gasotransmitters, highlighting plant physiological responses. This is an essential resource for students, researchers and agronomists interested in plant physiology, biochemistry and plant hormones.
Keywords: Gasotransmitters; Arsenic Toxicity; Plants; Biology; Biotechnology